Strengthening Micro, Small, and Medium Enterprises (MSMEs) in Response to the Policies on the Use of Domestic Products (Case Studi in Bekasi City) - Ikhsan, M.; Akbar, Taufik; Devianka, Meitha; Imam Abdullah, Raja (KnE Social Sciences, 2024)
The study aims to describe the strengthening of MSMEs carried out by the Bekasi City government in terms of capital, products, and marketing in response to policies on using domestic products within the Bekasi City government. The research used a qualitative approach. Primary data were collected using in-depth interviews with selected informants from local governments, SMEs, and academia. These are the people related to the management of MSMEs so that they understand about the various problems of MSMEs. Secondary data came from electronic media and relevant regional organizations. The data were analyzed using qualitative descriptive analysis. This research found that the Bekasi City government has made various efforts to strengthen MSMEs in Bekasi through the DKUKM. On the product side, socialization and training on home industry food (P-IRT) and P-IRT certification are given to the MSMEs, training is also carried out to improve packaging management capabilities and socialize halal certificates. On the capital side, the Bekasi City government prepares funds for capital through Bank Syariah Patriot, as well as training in preparing financial reports for lending funds to banks. Meanwhile, on the marketing side, the DKUKM Bekasi City held various promotions such as exhibitions, Ramadhan bazaars, bazaars in commemoration of the 25th anniversary of Bekasi City, training on making business identification numbers (NIB), digital marketing training, entrepreneurship training or workshops, socialization and training of home industry food certification (PIRT), training on using Shopee for MSMEs, and curation of the MSME products. Using a qualitative approach, this research can explore more stakeholder views related to the strengthening of MSMEs in response to policies on the use of domestic products, so that it gives different contributions to the theories and practices of the MSMEs development in Indonesia. Keywords: micro small and medium enterprises (MSME), strengthening, domestic products